Undang-Undang Pesantren Sebagai Landasan Pembaruan Pondok Pesantren di Indonesia (Studi Kebijakan UU No. 18 Tahun 2019) - Sahara Adjie Samudera (Fahima, 2023)
This article uses qualitative research methods with a literature study approach. The results of the analysis show that pesantren (Islamic boarding schools) are educational institutions that aim to explore Islamic religious science and practice it as a guide for daily life by emphasizing morals in society through the teaching of classical Islamic books by kyai and generally living in a dormitory. The implementation of education in Islamic boarding schools is regulated in UU Pesantren No. 18/2019 concerning Islamic Boarding Schools. The ratification of this law is an effort by the Indonesian government to strengthen the existence of Islamic boarding school education. The Pesantren Law explains that pesantren mainly carry out the function of education, the function of proselytizing, and the function of community empowerment. The development of Islamic boarding school education in the modern era is marked by the presence of Islamic boarding schools that use a formal education system like schools and madrasahs. However, the implementation of Islamic boarding schools faces several problems that are often discussed, such as the governance of Islamic boarding school education, infrastructure, and education financing. These issues were discussed and gave birth to efforts to renew and modernize Islamic boarding schools which include: reform and reformulation of the objectives of pesantren education in order to strengthen the position of pesantren as an established, world-oriented Islamic educational institution and the hereafter. The next step of renewal is taken through the transformation of the pesantren education system which is considered too classical and traditional towards a modern education system and supports 21st-century skills. In addition, it is important to transform the management system of pesantren, adjust the facilities and infrastructure of pesantren, etc.